Students' attitude towards taking up physical activities apart from university classes - Mariola Duda; Michał Rżany; Aleksandra Dudło; Krzysztof Suszyński; Dariusz Górka; Aleksandra Dogońska (Nicolaus Copernicus University in Toruń, 2015)
The aim of this study was to answer the following questions: What are the reasons that determine the physical activity of students outside of their university? What determines the duration of exercises and during what year the students exercise the most ? 301 students were tested using an original questionnaire. The analysis consisted of descriptive statistics and performed  analysis ANOVA. Analysis showed a significant relationship between sex and physical activity. Men are more likely to exercise. However, there is no relationship between the frequency of physical activity and gender.